Pengembangan LMS Berbasis Moodle Dengan Model Project Based Learning Untuk Meningkatkan Hasil Belajar Murid Pada Pembelajaran Pemrograman Antarmuka Pengguna (Studi Kasus: SMKS PGRI 2 Sidoarjo) - Amanda Rizky Putri Wibowo; Rindu Puspita Wibawa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
GUI Programming instruction for Grade XI RPL students at SMKS PGRI 2 Sidoarjo remained lecture-centered without a Learning Management System (LMS), resulting in low learning outcomes. This study aims to develop a Moodle-based LMS, GUILearn, integrated with the Project Based Learning (PjBL) model to improve learning outcomes and user experience. The Research and Development method was applied using the ADDIE model and a one-group pretest-posttest design involving 30 students. Data were analyzed through expert validation, the Wilcoxon Signed-Rank Test, N-Gain analysis, and the User Experience Questionnaire (UEQ). Validation results show the LMS is highly feasible (media 92.5%; materials 89%; test items 96%; module 95.45%). Learning outcomes improved significantly (mean score 49.00 to 82.83; W = 465, p < 0.001; 80% meeting the minimum criterion; N-Gain 0.6645, medium category). UEQ results showed five dimensions rated Good to Above Average, while Attractiveness remained Below Average (1.11). GUILearn proved effective in improving cognitive learning outcomes with an overall positive user experience.